Simulation of nitrate reduction in groundwater – An upscaling approach from small catchments to the Baltic Sea basin. (January 2018) - Hansen, A.L.; Donnelly, C.; Refsgaard, J.C.; Karlsson, I.B.
Highlights: Spatially targeted regulation of agricultural practices can decrease N-loads. We use local-scale models to simulate impact of a spatially targeted regulation. We develop a methodology to upscale knowledge from local- to large-scale models. The upscaling enables E-HYPE to simulate the impact on N-loads to the Baltic Sea. Abstract: This paper describes a modeling approach proposed to simulate the impact of local-scale, spatially targeted N-mitigation measures for the Baltic Sea Basin. Spatially targeted N-regulations aim at exploiting the considerable spatial differences in the natural N-reduction taking place in groundwater and surface water. While such measures can be simulated using local-scale physically-based catchment models, use of such detailed models for the 1.8 million km 2 Baltic Sea basin is not feasible due to constraints on input data and computing power. Large-scale models that are able to simulate the Baltic Sea basin, on the other hand, do not have adequate spatial resolution to simulate some of the field-scale measures. Our methodology combines knowledge and results from two local-scale physically-based MIKE SHE catchment models, the large-scale and more conceptual E-HYPE model, and auxiliary data in order to enable E-HYPE to simulate how spatially targeted regulation of agricultural practices may affect N-loads to the Baltic Sea. We conclude that the use of E-HYPE with this upscaling methodology enables the simulation of the impact on N-loads of applying a spatially targeted regulation at the Baltic Sea basin scale to the correct order-of-magnitude. The E-HYPE model together with the upscaling methodology therefore provides a sound basis for large-scale policy analysis; however, we do not expect it to be sufficiently accurate to be useful for the detailed design of local-scale measures. Graphical abstract: Image, graphical abstract